THE SOFSKILL MODEL FOR PREPARING GRADUATES WITH COMPETITIVENESS IN REALIZING SOCIETY 5.0 (Economic Education Faculty of Economics and Business Universitas PGRI Sumatera Barat, 2019)
The 4.0 industrial revolution causes disruption or disruption not only in the field of business models, but also the labour market in the next five years with enormous changes. Not after the hustle bustle of the 4.0 industrial Revolution, which is accompanied by the development of the disruption era, suddenly the emergence of the concept of realizing Society 5.0. In this concept, man will play a bigger role with big data transformation into a new wisdom that ultimately increases human capacity to, opening opportunities for humanity to achieve meaningful life, which will Improve the live, and the way we work.Rapid changes in the workplace as a result of globalization and revolution in technology and other disciplines demanded anticipation and revitalization including the field of education in preparing a reliable graduate of the working as of market. In this era, the development of education enters a very important time, not only in providing quality and optimal services, but also a challenge for education organizers is able to be accepted graduates in the world of work With the level of competition between domestic and foreign universities that quality in accordance with global career standards, but the problem until now occurs disparity between the needs of work market with the skills Prepared by our higher education system. This research aims to make the design of students soft skills integrated in every course taught in universities that can be used as an entry point in the achievement of graduates who have a competitive and knowledgeable Global according to the needs of the employment market in the realizing Society 5.0.